Scientific school of academician L.A. Orbeli in Petrograd – Leningrad (to hundredth anniversary of its creation) - V. V. Kolbanov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Basic stages of creation, development and spreading of academician L. A. Orbeli scientific school at Petrograd - Leningrad were traced. Significance of main scientific researches of this school in the physiology for the development of adjacent areas of medicine and biology was shown.